2020
DOI: 10.1371/journal.pone.0221851
|View full text |Cite
|
Sign up to set email alerts
|

Targeting chondroitinase ABC to axons enhances the ability of chondroitinase to promote neurite outgrowth and sprouting

Abstract: Background There is currently no effective treatment for promoting regeneration of injured nerves in patients who have sustained injury to the central nervous system such as spinal cord injury. Chondroitinase ABC is an enzyme, which promotes neurite outgrowth and regeneration. It has shown considerable promise as a therapy for these conditions. The aim of the study is to determine if targeting chondroitinase ABC expression to the neuronal axon can further enhance its ability to promote axon outgrowth. Long-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Recent advances in the deployment of the chABC enzyme show promise. By targeting chABC to axons, neurite extension in SH-SY5Y neurons was significantly increased, even over cells that were transfected with a non-targeted variant of the enzyme ( Day et al, 2020 ). Despite the successes in animal models, no clinical trials using the enzyme have been reported.…”
Section: Role Of Cspg In Recovery After Cns Injurymentioning
confidence: 99%
“…Recent advances in the deployment of the chABC enzyme show promise. By targeting chABC to axons, neurite extension in SH-SY5Y neurons was significantly increased, even over cells that were transfected with a non-targeted variant of the enzyme ( Day et al, 2020 ). Despite the successes in animal models, no clinical trials using the enzyme have been reported.…”
Section: Role Of Cspg In Recovery After Cns Injurymentioning
confidence: 99%
“…RhoA/ROCK signaling has been implicated in Aβ‐induced responses of microglial cells (Zhang et al, 2019). As ChABC treatment may abrogate activation of RhoA‐ROCK pathway by chondroitin sulfates via PTPσ (Pendleton et al, 2013) and reduce expression of RhoA (Day, Alves, Daniell, Dasgupta, & Ogborne, 2020), we shall further investigate the relevance of this pathway in early microglia migration defects in AD mouse models and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of CS from the defect site by these enzymes resulted in recovery of neural functional properties [ 260 , 263 , 264 , 265 ]. Acute trauma to the brain and upper limbs resulting in neural damage have also been treated using chondroitinase ABC [ 266 , 267 ], resulting in neural sprouting through the defect site [ 268 ] and functional recovery [ 269 ].…”
Section: Tissue Therapeutic Interventions Involving Csmentioning
confidence: 99%